2018
DOI: 10.4314/ahs.v17i4.7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>mecA </i> gene among <i>staphylococci </i> from clinical samples of a tertiary hospital in Benin City, Nigeria

Abstract: BackgroundThe staphylococci have increasingly been associated with infections worldwide and anti-microbial resistance has made these versatile pathogens more recalcitrant in the hospital setting.ObjectivesThis study sought to investigate the occurrence and distribution of Staphylococcus species as well as determine the prevalence of methicillin resistant Staphylococcus aureus (MRSA) and methicillin resistant coagulase negative staphylococci (MRCoNS) among clinical samples from University of Benin Teaching Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
28
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 22 publications
13
28
4
Order By: Relevance
“…A review paper [ 2 ] based on 35 studies in Africa, describing epidemiologically relevant CoNS found the most abundant CoNS species to be S. epidermidis and S. haemolyticus but found low detection rates of S. capitis (three studies), S. lugdunensis (three studies), S. caprae (one study), and S. gallinarum (one study). The MRCoNS prevalence rate (76.4%) was higher than that found in previous studies from clinical samples in healthcare settings in Nigeria (46.3%) [ 11 ] and Egypt (75.9%) [ 9 ]. However, higher MRCoNS prevalence figures of 86% [ 12 ] and 100% [ 13 ] were detected for CoNS implicated in infections in South Africa.…”
Section: Discussioncontrasting
confidence: 64%
“…A review paper [ 2 ] based on 35 studies in Africa, describing epidemiologically relevant CoNS found the most abundant CoNS species to be S. epidermidis and S. haemolyticus but found low detection rates of S. capitis (three studies), S. lugdunensis (three studies), S. caprae (one study), and S. gallinarum (one study). The MRCoNS prevalence rate (76.4%) was higher than that found in previous studies from clinical samples in healthcare settings in Nigeria (46.3%) [ 11 ] and Egypt (75.9%) [ 9 ]. However, higher MRCoNS prevalence figures of 86% [ 12 ] and 100% [ 13 ] were detected for CoNS implicated in infections in South Africa.…”
Section: Discussioncontrasting
confidence: 64%
“…The mechanisms of resistance included mecA (≥107), blaZ ( n = 284), dfrA (≥5), and dfrG (≥152). Colonized persons—including immune‐compromised individuals—facilitated the spread of S. aureus and MRSA ST8, identified as ubiquitous in various geographic areas of Nigeria . High utilization of cotrimoxazole or SXT, because of low cost and easy obtainability through lenient medication regulations, was implicated for the high resistance .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the mecA gene was successfully amplified in 11 out of 19 tested isolates (57.89%) at 583 bp. A comparative study in Nigeria reported that the mecA gene was prevalent in 38% of S. aureus isolates from human clinical specimens [ 49 ]. In Egypt, 8 out of 19 (42.1%) food origin S. aureus isolates exhibited phenotypic resistance to oxacillin and carried the mecA gene [ 50 ].…”
Section: Discussionmentioning
confidence: 99%